Learning Management in Salaf Islamic Boarding Schools - Moh. Yamin (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
This study aims to find out and obtain an overview of learning in salaf islamic boarding schools by focusing on goals, educators, students, materials, methods and evaluations. The method used in this study is a descriptive method with a qualitative approach. The data processed comes from interview, observation and docamimetic data. The result of this research is that Pesantren Miftahul Huda aims to produce students to become Alamilin Scholars (scholars who are able to practice their knowledge), Imam Al Muttaqīn (leading people to piety), and Muttaqīn (devout persons). Pondok Pesantren Miftahul Huda has 5000 students from men and women from various regions. The three stages of learning applied are: (1) providing guidance and teaching; (2) habituation; and (3) formation. The learning method used is the classical method, namely, lectures, sorogan, and bandongan. The results of research or learning evaluations that are applied are weekly and semesterly evaluations. The benchmark in the success of this Pesantren is alumni who are independent and can create a tawhid-based society by establishing a pesantren.